Benang Merah dan Jalan Berbeda: Pendidikan Agama Islam di Indonesia dan Malaysia - Darmadi, Dadi (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2020)
Azmil Tayeb. 2018. Islamic Education in Indonesia and Malaysia: Shaping Minds, Saving Souls. New York: Routledge.Many studies have been done to compare the similarities and differences of institutional systems in two or more countries, but not all of them succeed in describing in detail what, how and why the things being studied are the same or different. This very interesting book with a broad scope covers this challenge quite convincingly. Namely, there are common threads in the Islamic education system in Indonesia and Malaysia, but some of these factors are the reasons why the two religious education systems then take different paths: (1) the ideological factors that oversee it, (2) the forms of Islamization that create different responses to the state, and (3) the central government’s control of resources that influence central-regional relations. The author successfully presents a complex but vivid nuance of how Indonesia and Malaysia, which are geographically and culturally close, have eventually displayed different faces of Islamic education.